Level and method of feeding dehydrated alfalfa pellets as a protein supplement for beef cows grazing winter flint hills range - E.S. Vanzant; R.C. Cochran; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1990)
Four winter protein supplementation schemes were studied using 116 beef cows grazing Flint Hills range. The treatments were: 1) 4.0 lb soybean meal/sorghum grain (27.3% crude protein (CP» per head daily (SS), 2) 4.0 lb dehydrated alfalfa pellets (DEHY. 20.0% CP) per head daily (LO-DEHY), 3) 5.5 lb DEHY per head daily (HI-DEHY), and 4) DEHY fed at levels calculated to provide 4.0 lb per head daily with less fed in early winter and more fed in late winter (STAGGER-DEHY). The HI-DEHY and SS treatments resulted in higher (P.10) for the LO-DEHY and STAGGER-DEHY groups. Cow reproductive performance and calf birth weights and average daily gains were unaffected (P>.10) by the treatments. All of the supplementation schemes evaluated in this experiment appeared relatively satisfactory, given the initial condition of the cows. However, the higher levels of nutrient supplementation (HI-DEHY and SS; 1 lb CP/d) would probably sustain reproductive performance at a higher level over an extended period of time. Additionally, when DEHY was fed at the low level, altering the schedule of feeding over the winter did not appear to affect cow performance.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Cows; Protein supplements; Dehydrated alfalfa pellets; Winter range